2022
DOI: 10.3390/vaccines10040502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Humoral Immune Response of a Heterologous Vaccination between BBIBP-CorV and BNT162b2 with a Temporal Separation of 7 Months, in Peruvian Healthcare Workers with and without a History of SARS-CoV-2 Infection

Abstract: Information on the effects of a heterologous booster in adult patients first vaccinated with the BBIBP-CorV vaccine is limited. This prospective cohort study evaluated the humoral response of 152 healthcare workers (HCWs) from a private laboratory in Lima (Peru) before and after receiving the BNT162b2 vaccine, with a seven-month interval since the BBIBP-CorV doses. We employed the Elecsys® anti-SARS-CoV-2 S and the cPass™ SARS-CoV-2 Neutralization Antibody (NAbs) assays to evaluate anti-S-RBD IgG and NAbs, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…This phenomenon has been well-described, even for people primed with inactivated vaccines such as BBIBP-CorV. For instance, a Peruvian one-arm study reported a strong humoral response after a heterologous BNT162b2 booster in HCWs primed with the inactivated BBIBP-CorV vaccine (11), even higher than the 17-fold increase found in our study. In Lebanon, a prospective cohort study comparing a BNT162b2 booster versus no booster in BBIBP-CorV vaccinated people, found that boosting elicited higher anti-spike IgG geometric mean titers: 8040 BAU/mL (95%CI: 4612–14016) versus 1384 BAU/mL (95%CI: 1063–1801) p<0.001 (12).…”
Section: Discussionsupporting
confidence: 53%
“…This phenomenon has been well-described, even for people primed with inactivated vaccines such as BBIBP-CorV. For instance, a Peruvian one-arm study reported a strong humoral response after a heterologous BNT162b2 booster in HCWs primed with the inactivated BBIBP-CorV vaccine (11), even higher than the 17-fold increase found in our study. In Lebanon, a prospective cohort study comparing a BNT162b2 booster versus no booster in BBIBP-CorV vaccinated people, found that boosting elicited higher anti-spike IgG geometric mean titers: 8040 BAU/mL (95%CI: 4612–14016) versus 1384 BAU/mL (95%CI: 1063–1801) p<0.001 (12).…”
Section: Discussionsupporting
confidence: 53%
“…The “similar” relative effectiveness between the different combinations is also an interesting finding, as mRNA vaccines are, in general, more effective than the other types of vaccines for preventing both infection and death [24] , [41] . However, in our study, the mix and match of both an inactivated virus vaccine with a third dose of an mRNA vaccine, and a viral vector vaccine with a third dose of an mRNA vaccine, showed equivalent effectiveness for the prevention of death due to COVID-19 with three doses of an mRNA vaccine.…”
Section: Discussionmentioning
confidence: 89%
“…However, the evaluation of the peculiar mixture of vaccines generated in Peru is relevant, since few countries have applied the combination of receiving an mRNA vaccine after an initial schedule of BBIBP-CorV. Moreover, most studies assessing these combinations focus primarily on immunogenicity and safety rather than effectiveness [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to assess the neutralizing capacity induced by vaccination and natural infection by using a standardize commercial surrogate virus neutralization test (sVNT) [17]. The sVNT has been designed as a powerful alternative to the conventional plaque reduction neutralization test (PRNT) to measure neutralizing antibodies post-infection to SARS-CoV-2 [19][20][21][22], and in vaccinated individuals [23][24][25]. In addition, the design of the GenScript sVNT ELISA is adapted to determine the difference in binding inhibition to compare vaccines and infecting SARS-CoV-2 variants antibody responses.…”
Section: Discussionmentioning
confidence: 99%